Decipher non‐canonical SPAST splicing mutations with the help of functional assays in patients affected by spastic paraplegia 4 (SPG4). Issue 2 (6th May 2022) - Ferese, Rosangela; Scala, Simona; Suppa, Antonio; Campopiano, Rosa; Asci, Francesco; Chiaravalloti, Maria Antonietta; Zampogna, Alessandro; D'Alessio, Carmelo; Fittipaldi, Filomena; Buttari, Fabio; Di Pardo, Alba; Giardina, Emiliano; et al.
Abstract : Flowchart showing the molecular approach used to decipher the non‐canonical splicing mutations.